Pengembangan Media Pembelajaran Komik Berbasis Qr Code pada Mata Pelajaran PPKn Kelas III SD - Faizal Tri Haryanto; Leo Charli; Armi Yuneti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop a comic learning media design based on Qr Code. Testing the validity and practicality of Qr Code based comic media in Class III PPKn lessons at SD N 1 Marga Sakti. This type of research is Research and Development with a 4-D (Four-D) development model. The subjects of this study were media experts, linguist, material expert, teachers, third grade students at SD N 1 Marga Sakti. Data collection techniques using interviews and questionnaires. Based on the results of the validity assessment conducted by the three experts, namely media experts who scored 0.76 with the classification